2005
DOI: 10.1021/ol0522743
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a Chiral Copper Reagent Derived from Propargylic Oxazolidininone to Aldehydes

Abstract: [reaction: see text] The copper reagent arising from an optically pure propargylic oxazolidinone was found to react regio- and diastereoselectively with aldehydes, leading, in a one-pot procedure, to the anti homopropargylic amino alcohols derivatives in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Vrancken and Mangeney 77 found that lithiated allemamides generated from the propargyl amide 228 could undergo aldol reactions in the presence of CuCN to afford anti -homopropargyl amino alcohols 241 with high yields and diastereoselectivities (Scheme 68). In most cases, the addition proceeds through the favored transition state anti a 241 .…”
Section: Reactions Of Allenamidesmentioning
confidence: 99%
“…Vrancken and Mangeney 77 found that lithiated allemamides generated from the propargyl amide 228 could undergo aldol reactions in the presence of CuCN to afford anti -homopropargyl amino alcohols 241 with high yields and diastereoselectivities (Scheme 68). In most cases, the addition proceeds through the favored transition state anti a 241 .…”
Section: Reactions Of Allenamidesmentioning
confidence: 99%
“…Finally, a chiral version of this reaction could be proposed, starting from an enantiopure propargylic oxazolidinone. 7 As shown in Tables 1 and 2, the anti/syn ratio (ca. 95:5), seems to be more or less insensitive to the nature of the aldehyde, with the exception of butanal (R 2 = n-Pr, Table 2), which reacts with the cyanocuprates derived from propargylic ethers 4a-c to give the homopropargylic alcohols 5 in an anti/syn ratio of only 90:10.…”
Section: Preparation Of Anti-12-disubstituted Homopropargylic Alcohomentioning
confidence: 88%
“…The lithiation can be performed with s-BuLi at −78 • C and the amino alkyllithium can be trapped with electrophiles and undergoes conjugate addition to α,β-unsaturated carbonyls upon transmetallation with Cu salts (Scheme 7.39). N-propargyl oxazolidinones are also easily lithiated α to nitrogen to furnish useful synthetic intermediates that can be trapped with a range of electrophiles [52]. The lithiation of the chiral oxazolidinone 18 leads to the propargyllithium intermediates 18-Li, whose real structure remains unknown, and could be in equilibrium with the corresponding allenyllithium 19-Li that reacts with an aldehyde to furnish almost exclusively the corresponding allenic alcohol 20.…”
Section: Lithiation Of Acyclic Aminesmentioning
confidence: 99%